IMPEMENTASI PROGRAM RUMAH LAYAK HUNI DI KABUPATEN KAMPAR - Samosir, Siska Indriyani; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Livable Housing Program is a program organized by the government of Kampar regency in order to realize decent housing for the poor. Then the government through the Department of Human Settlements and Spatial Kampar regency make policy regarding Livable Housing Program which is stipulated in Kampar Regent Number: 648 / ckTR-SET / 2015/937 Guidelines On Development Aid Livable house. But in the year 2012 to 2014 before the decree was issued, the program is still using the Handbook of Development Assistance Livable house. This study aims to determine Livable Housing Program Implementation in Kampar regency and to determine the factors inhibiting Livable Housing Program Implementation in Kampar regency.In a theoretical model of implementation by George C. Edward in Widodo (2011: 96-110), there are four critical variables in the implementation of public policies or programs that establish linkages with each other to achieve the purpose of implementation of the policy, namely communication, resources, disposition, and structure bureaucracy.The method used in this research is qualitative research. With the technique done of snowball sampling, the key informant in this study. In this study, the informant is the Head. Cipta Karya, Kasi. Housing and Resettlement, Local Community Organizations (OMS) and Recipient Livable Housing Program.Based on the research and discussion that researchers do in the field, it was found that the Program Implementation Livable house in Kampar regency has not been implemented to the fullest. That's because various factors that hinder the implementation of this program is difficult implemented optimally.Keywords: Implementation, Program, Home Livable